2018
DOI: 10.1186/s13046-018-0879-z
|View full text |Cite
|
Sign up to set email alerts
|

MiR-452 promotes an aggressive colorectal cancer phenotype by regulating a Wnt/β-catenin positive feedback loop

Abstract: BackgroundAberrant activation of Wnt/β-catenin signaling pathway is considered to be an important issue in progression and metastasis of various human cancers, especially in colorectal cancer (CRC). MiR-452 could activate of Wnt/β-catenin signaling. But the mechanism remains unclear.MethodsThe expression of miR-452 in CRC and normal tissues was detected by real-time quantitative PCR. The effect of miR-452 on CRC growth and invasion was conducted by functional experiments in vitro and in vivo. Bioinformatics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 36 publications
1
23
1
Order By: Relevance
“…Since T cell factor/lymphatic enhancement factor is an effective transcription factor in the miR-452 promoter, in turn, miR-452 transcription is promoted by Wnt signaling, forming a positive feedback loop. 46 In addition, a negative feedback loop was found between the miRNA and Wnt signaling pathway. miR-145, a tumor suppressor miRNA, can interact with TCF4-β-catenin complex, recruit polycomb repressive complex 2 (PRC2) histone trimethylase, and suppress Wnt signal transduction.…”
Section: Wnt Signaling and Micro-rnasmentioning
confidence: 99%
“…Since T cell factor/lymphatic enhancement factor is an effective transcription factor in the miR-452 promoter, in turn, miR-452 transcription is promoted by Wnt signaling, forming a positive feedback loop. 46 In addition, a negative feedback loop was found between the miRNA and Wnt signaling pathway. miR-145, a tumor suppressor miRNA, can interact with TCF4-β-catenin complex, recruit polycomb repressive complex 2 (PRC2) histone trimethylase, and suppress Wnt signal transduction.…”
Section: Wnt Signaling and Micro-rnasmentioning
confidence: 99%
“…qRT-PCR was performed on the Applied Biosystems 7500 Sequence Detection system with IQTM SYBR Green Supermix (Bio-Rad Laboratories, Hercules, CA, USA) and 5 ng of cDNA and 10 pM of each primer. The cycling conditions were set as previously described [20]. The data were normalized to the geometric mean of the housekeeping gene GAPDH or to U6 small nuclear RNA expression and calculated according to the 2 -ΔΔCT method.…”
Section: Rna Extraction and Qrt-pcrmentioning
confidence: 99%
“…Studies have shown that miR-92a-3p is upregulated in CRC and promotes the migration of CRC by targeting NF2 (Alcantara and Garcia, 2019). MiR-452 activates Wnt/ β-catenin to promote CRC metastasis (Li et al, 2018a). In addition to upregulated miRNAs, downregulated miRNAs such as miR-144 , miR-548c-5p , and miR-198 also play important roles in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%